Perceived fidelity of compressed and reconstructed radiological images: A preliminary exploration of compression, luminance, and viewing distance - Pilgram, Thomas K.; Slone, Richard M.; Muka, Edward; Cox, Jerome R.; Blaine, G. James (Journal of digital imaging, 1998)
The authors' goal was to explore the impact of image compression algorithm and ratio, image luminance, and viewing distance on radiologists' perception of reconstructed image fidelity. Five radiologists viewed 16 sets of four hard-copy chest radiographs prepared for secondary interpretation. Each set included one uncompressed, and three compressed and reconstructed images prepared using three different algorithms but the same compression ratio. The sets were prepared using two subjects, four compression ratios (10:1, 20:1, 30:1, 40:1), and two luminance levels (2,400 cd/m2, standard lightbox illumination, and 200 cd/m2, simulating a typical CRT display). Readers ranked image quality and evaluated obviousness and clinical importance of differences. Viewing distances for image screening, inspection, and comparison were recorded. At 10:1 compression, the compressed and uncompressed images were nearly indistinguishable; the three algorithms were very similar, and differences were rated "not obvious" and "not important." At higher compression, readers consistently preferred uncompressed images, with notable differences between algorithms. The obviousness and clinical importance of differences were rated higher at lightbox luminance. Viewing distances appeared to be idiosyncratic.